HIGH SCHOOL STUDENTS’ READINESS FOR DISTANCE LEARNING - Akdogan, Ali (International Online Journal of Education and Teaching, 2021)
The purpose of this study was to determine high school students for distance learning. Mainly due to the study a multidimensional instrument for high students’ readiness for distance learning (HRD) developed and validated. The study adopted qualitative research method based on quantitative data. The participants of the study comprised 191 high school students who were selected using randomly sampling model. The data were collected via readiness for distance learning scale (HRD) and analyzed using exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) to establish the construct validity of the HRD model. In addition, a series of one-way ANOVA were conducted to investigate the effect of demographic variables on readiness of distance learning. Through confirmatory factor analysis, HRD was validated in three dimensions: communication, access and motivation. In this study, high school students’ mean scores in three dimensions are all higher than the theoretical mean of 3, ranging from 3.60 to 4.37 on a 5-point scale as X̄= 40.64 (SS=8.80).This finding means that the current study’s sample of high school students has the highest readiness in the dimension of access X̄=16.98 (SS=4.64), followed by motivation X̄=12.86 (SS=4.66); communication X̄=10.79 (SS=2.45. The significant differences were observed that high school students are those who study at 9. grade had greater readiness than high school students are those who study at 11. grade in high schools whereas high school students are those who study at 11. grade in high schools had greater readiness than high school students are those who study at 10. and 12. grade in high schools according to means score of HDR. It was also found out that perception of students’ self-confidence while using computer caused significant statistical differences in three dimensions of HRD; the students who had higher level (very good, good) of self-confident while using computer exhibited significantly greater readiness than those who had lower level of self-confident while using confidence. Meanwhile, high school students are those who had study habit reached greater point from HDR scale than high school students who had not study habit (t (188) = 5.29, p = .00,d=.08).